Influence of the contact area of the sub-antral space with sinus bone and the Schneiderian membrane on osteogenesis in lateral window sinus elevation surgery: a prospective experiment - Xiao She; Dongjiao Zhang; Xin Xu; Zhanwei Zhang; Chonghao Ji; Zechuan Li; Dawei Song (BMC, 2022)
Abstract Background Osteogenesis of lateral window sinus elevation surgery is the key to placement of the subsequent implant, excessive collapse of the sub-antral space may adversely affect long-term stability of implants. At present, few studies focus on the influence of the contact area of the sub-antral space on osteogenesis. This study evaluated whether the change in the contact area of the sub-antral space with maxillary sinus bone and the Schneiderian membrane can affect osteogenesis. Methods Cone beam computed tomography (CBCT) images were collected of patients requiring maxillary sinus floor elevation (residual bone height < 6 mm) for standard-length implant placement before surgery, after surgery, and at 6-month follow-up visits. The postoperative sub-antral space volume (V1) and surface area (S1), and the remaining volume after six months of healing (V2) were measured. Then, the contact area of sub-antral space with maxillary sinus bone (Sbc) and the Schneiderian membrane (Smc), the absorbed volume during healing (Va), and the percentage of remaining volume (V2%) and absorbed volume (Va%) were calculated. The correlation between anatomical parameters was analyzed using multiple linear regression. Results A total of 62 maxillary sinuses from 56 patients were augmented, of which 57 were considered for the final analysis (5 withdrew due to perforation). Multiple linear regression results demonstrated that Sbc was significantly positively correlated with Va (β coefficient = 0.141, p < 0.01) without correlation between Smc and Va (β coefficient =  − 0.046, p = 0.470). There was a positive correlation between Sbc and V2% (β coefficient = 2.269, p < 0.05). Conclusions This study confirmed that the size of the Sbc in lateral window sinus elevation surgery affected osteogenesis after six months of healing. Clinicians should assess the sinus contour type preoperatively, then consider whether it is necessary to expand the range of the Schneiderian membrane elevation to avoid excessive collapse of the sub-antral space. Trial registration: Chinese Clinical Trial Registry (ChiCTR), ChiCTR2200057924. Registered 22 March 2022-Retrospectively registered.